House price growth when children are teenagers: A path to higher earnings? - Daniel Cooper; María José Luengo-Prado (Federal Reserve Bank of Boston, 2014)
The United States has a long history of promoting homeownership through the mortgage interest tax deduction, and home equity constitutes an important source of borrowing collateral. There is a sizable body of work studying how fluctuating house prices impact consumer behavior. Since college tuition costs pose a large financial burden for many U.S. families, access to housing equity may impact decisions about pursuing a post-secondary education. This paper adds to the literature by using MSA-level house-price variation and data from the Panel Study of Income Dynamics to study the link between future adult earnings and the house price growth that occurs around the time children are 17 years-old, when most college enrollment decisions are made, and how this link varies based on whether parents own or rent their homes. The sample period runs from 1979 through 1999.
Keywords: E21; I22; I24; 330